Polytrimethylene terephthalate fiber, method for producing same, air-blended yarn comprising same, and fabric comprising same

By controlling the boiling water shrinkage rate and elongation rate of 20% of the elastic modulus of polypropylene terephthalate fiber, and combining air-blended fiber technology and irregular cross-section fibers, a fabric with low shrinkage and high softness was manufactured. This solved the problems of insufficient fiber softness and high heat shrinkage rate in the existing technology, and achieved stable production and soft drape.

CN121002238APending Publication Date: 2025-11-21TEIJIN FRONTIER CO LTD

Patent Information

Application Number
CN202480025004.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-11
Filing Date
2024-04-02
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing poly(propylene terephthalate) fibers, when made into fabrics, lack sufficient softness and have a high heat shrinkage rate, leading to fabric hardening or difficulty in stable production.

Method used

By controlling the boiling water shrinkage and elongation of poly(propylene terephthalate) fibers within a specific range, and combining air-blended fiber technology with profiled cross-section fibers and core-sheath structures, the thermal stress and shrinkage of the fibers are controlled to manufacture fabrics with low shrinkage and high softness.

Benefits of technology

It achieves low shrinkage and soft texture in fabrics, solving the problems of insufficient fiber softness and high heat shrinkage in existing technologies, and improving fiber stability and soft drape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a low-shrinkage fiber; a method for producing the low-shrinkage fiber; an air-blended yarn comprising the polytrimethylene terephthalate fiber; and a fabric comprising the air-blended yarn. The low-shrinkage fiber is substantially composed of polytrimethylene terephthalate, and can be used to produce a precursor for a fabric, which has a soft texture and a low shrinkage rate due to heat. The present invention is characterized in that 90 mol% or more of polytrimethylene terephthalate fibers are composed of trimethylene terephthalate repeating units, the boiling water shrinkage of the polytrimethylene terephthalate fibers is 5% or less, and the elastic modulus of the polytrimethylene terephthalate fibers at an elongation of 20% is 5 cN / dtex or less.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a fiber consisting essentially of polytrimethylene terephthalate, which is a precursor fiber for a cloth having a small shrinkage rate caused by heating and a soft texture, and a manufacturing method thereof, and an air mixed filament comprising the polytrimethylene terephthalate fiber and a cloth consisting of the air mixed filament. BACKGROUND

[0002] Polytrimethylene terephthalate (hereinafter, sometimes referred to as PPT) has properties similar to polyamide, such as excellent elastic recovery and dyeability, and properties similar to polyethylene terephthalate, such as light resistance, heat set property, dimensional stability, and low water absorption, and thus applications thereof in various fields such as BCF carpets and brushes have been proposed (for example, Japanese Patent Application Publication No. 9-3724, Japanese Patent Application Publication No. 8-173244, Japanese Patent Application Publication No. 5-262862, and the like). In addition, polytrimethylene terephthalate fiber has a low Young's modulus, and thus a product having a soft texture can be obtained.

[0003] Further, as a method for manufacturing polytrimethylene terephthalate fiber, a method in which undrawn yarn obtained by melt spinning at a speed of 300 to 4000 m / min is heat drawn at a temperature higher than the glass transition temperature of the undrawn yarn in one or more stages after being temporarily wound or continuously without being wound has been proposed. Also, as the spinning and drawing conditions at this time, for example, a method in which a polytrimethylene terephthalate polymer having an intrinsic viscosity [η] of 0.7 or more is drawn at a spinning speed of 3000 m / min, and after being continuously drawn at 70°C without being temporarily wound, relaxation heat treatment is performed at a relaxation rate of 6 to 20% has been disclosed in Japanese Patent Application Publication No. 2001-207329 (Patent Document 1).

[0004] However, the polytrimethylene terephthalate fiber proposed in the past has a low Young's modulus compared to polyethylene terephthalate fiber, and in the case where a cloth is produced, the characteristics thereof are not sufficiently exhibited, and a sufficiently satisfactory result has not been obtained in terms of softness.

[0005] On the other hand, a polytrimethylene terephthalate fiber having a soft texture has been disclosed in Japanese Patent Application Publication No. 2001-348729 (Patent Document 2) by being wound at a speed of 4500 m / min or more. Indeed, a soft cloth is obtained in this method, but there are problems such as tight winding, poor winding shape, and flattened paper tube due to elastic deformation of the yarn at the time of winding the yarn. In addition, since the spinning speed is fast, the yarn is easily broken, and it is difficult to stably produce the yarn.

[0006] PRIOR ART DOCUMENTS

[0007] PATENT LITERATURE

[0008] Patent Document 1: Japanese Patent Application Laid-Open (JP-A) No. 2001-207329

[0009] Patent Document 2: Japanese Patent Application Laid-Open (JP-A) No. 2001-348729 SUMMARY

[0010] The present application was accomplished in view of the above background, and aims to provide a low-shrinkage fiber consisting essentially of polytrimethylene terephthalate and capable of producing a yarn for cloth and the like having a small shrinkage due to heat and a soft texture, and an air-mixed yarn and cloth and the like containing the same.

[0011] The present inventors and others made intensive studies in order to solve the above problems, and as a result, found that when the boiling water shrinkage of a fiber consisting essentially of polytrimethylene terephthalate (hereinafter, sometimes referred to as "boiling water shrinkage") and the modulus of elasticity at 20% elongation of the polytrimethylene terephthalate fiber are controlled in ranges different from those of the so-called direct drawn yarn and high speed spun yarn described in the above prior art documents, a desired polytrimethylene terephthalate fiber can be obtained, thereby completing the present application.

[0012] Therefore, according to the present application, there are provided:

[0013] 1. A polytrimethylene terephthalate fiber, characterized by a polytrimethylene terephthalate fiber consisting of 90 mol% or more of trimethylene terephthalate repeating units, a boiling water shrinkage of 5% or less, and a modulus of elasticity at 20% elongation of 5 cN / dtex or less.

[0014] 2. The polytrimethylene terephthalate fiber according to the above 1, wherein the polytrimethylene terephthalate fiber has a birefringence Δn of 0.040 or more and a specific gravity of 1.350 or less.

[0015] 3. The polytrimethylene terephthalate fiber according to the above 1 or 2, wherein the polytrimethylene terephthalate fiber has a thermal stress peak at 50 to 100°C, and a peak value of the thermal stress of 0.2 cN / dtex or less.

[0016] 4. The polytrimethylene terephthalate fiber according to the above 1 or 2, wherein the polytrimethylene terephthalate fiber has a breaking strength of 1.5 to 3.5 cN / dtex and a breaking elongation of 30 to 100%.

[0017] 5. A method for producing polytrimethylene terephthalate fiber, characterized by melt-solidifying polytrimethylene terephthalate consisting of 90 mol% or more of polytrimethylene terephthalate repeating units, taking up at a take-up speed of 1000 m / min or more, and then stretching the polytrimethylene terephthalate by 1.1 times or more at a temperature below the glass transition point of the polytrimethylene terephthalate, and then shrinking the fiber by 0.5 to 0.9 times while heating.

[0018] 6. An air laid filament comprising the polytrimethylene terephthalate fiber according to any one of claims 1 to 4 and a polyester fiber.

[0019] 7. The air laid filament according to claim 6, wherein the polyester fiber has a boiling water shrinkage of 7 to 50%.

[0020] 8. The air laid filament according to claim 6 or 7, which contains a fiber having a non-circular cross section.

[0021] 9. A core-sheath type air laid filament, characterized by being obtained by subjecting the air laid filament according to claim 6 to a heat treatment, and being an air laid filament having a total denier of 30 to 400 dtex, which is composed of a core filament composed of a polyester fiber and a sheath filament composed of a polytrimethylene terephthalate fiber having a single fiber denier of 0.3 to 10 dtex, and having a filament length difference between the core filament and the sheath filament of 5% or more as defined by the following method.

[0022] (Measurement method of filament length difference)

[0023] After subjecting the air laid filament to treatment under boiling water, the air laid filament is cut to a length of 5 cm under a load of 0.1 cN (0.098 g) x the total denier (dtex) of the air laid filament, and a polyester fiber A (single fiber) and a polytrimethylene terephthalate fiber B (single fiber) are taken out from the cut air laid filament, and the length is measured under a load of 0.1 cN (0.098 g) x the single fiber denier (dtex) of each, and the filament length difference (%) is calculated by the following equation.

[0024] Filament length difference (%) = (LB - LA) / LA x 100

[0025] wherein LA is the filament length (cm) of the polyester fiber of the core filament, and LB is the filament length (cm) of the polytrimethylene terephthalate fiber of the sheath filament.

[0026] 10. The core-sheath type air laid filament according to claim 9, wherein the weight ratio of the sheath filament to the total weight of the core-sheath type air laid filament is 50 to 90%.

[0027] 11. The core-sheath type air laid filament according to claim 9 or 10, which contains a fiber having a non-circular cross section.

[0028] 12. A fabric comprising the air laid filament of any one of claims 6 to 8.

[0029] 13. A fabric comprising the core-sheath type air laid filament of any one of claims 9 to 11.

[0030] According to the present application, it is possible to provide a low shrinkage fiber and a manufacturing method thereof, the fiber consisting essentially of polytrimethylene terephthalate and capable of manufacturing a yarn for a fabric having a soft texture and a small shrinkage ratio caused by heat, and an air laid filament comprising the polytrimethylene terephthalate fiber and a fabric composed thereof. BRIEF DESCRIPTION OF DRAWINGS

[0031] Figure 1 is a schematic diagram showing an example of the irregularity in the irregular cross-section fiber used in the present application.

[0032] Figure 2 is a schematic diagram showing an example of the flatness in the flat cross-section fiber used in the present application. DETAILED DESCRIPTION

[0033] Hereinafter, the present application will be described in detail.

[0034] (1) Polymer raw material

[0035] The polymer used in the present application is polytrimethylene terephthalate (hereinafter, also referred to as PTT) consisting of 90 mol% or more of trimethylene terephthalate repeating units. Here, PTT refers to a polyester in which terephthalic acid is used as an acid component and trimethylene glycol (also referred to as 1,3-propanediol) is used as a glycol component. The PTT can contain 10 mol% or less of other copolymer components.

[0036] As such copolymer components, 5-sodium sulfonate isophthalic acid, 5-potassium sulfonate isophthalic acid, 3,5-dicarboxylic acid phenyl sulfonic acid tetrabutyl salt, 3,5-dicarboxylic acid phenyl sulfonic acid tributyl methyl salt, 1,4-butanediol, neopentyl glycol, 1,6-hexamethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexane dimethanol, adipic acid, dodecanedioic acid, 1,4-cyclohexane dicarboxylic acid, and the like ester-forming monomers can be mentioned.

[0037] In addition, various additives such as a matting agent, a heat stabilizer, an antifoaming agent, a color matching agent, a flame retardant, an antioxidant, an ultraviolet absorber, an infrared absorber, a crystal nucleating agent, a fluorescent whitening agent, and the like can be copolymerized or mixed in the PTT as needed.

[0038] The intrinsic viscosity [η] of the polytrimethylene terephthalate polymer used in the present application is preferably 0.5 to 1.6, more preferably 0.6 to 1.5. Further preferably, it is 0.7 to 1.4.

[0039] In the case where the intrinsic viscosity is less than 0.5, since the molecular weight of the polymer is too low, it is sometimes difficult to exhibit strength, on the other hand, if the intrinsic viscosity exceeds 1.6, since the flowability is low, the drawability of the low viscosity polytrimethylene terephthalate is impaired, and it sometimes becomes a cause of yarn breakage at the time of spinning, and thus is not preferable.

[0040] (2) Polytrimethylene terephthalate fiber

[0041] The polytrimethylene terephthalate fiber of the present application has small deformation due to hot water treatment, and thus when made into cloth, the yarn has less shrinkage and has a soft feel. In addition, since the modulus of elasticity after the first yield point in the tensile strength elongation measurement, which is a characteristic of the polytrimethylene terephthalate fiber, is low, if cloth using the same is produced, it becomes cloth having more soft drape than the usual polytrimethylene terephthalate fiber.

[0042] As the yarn properties of such a polytrimethylene terephthalate fiber, the boiling water shrinkage (hereinafter, sometimes referred to as boiling water shrinkage) of the polytrimethylene terephthalate fiber in the present application needs to be 5% or less, preferably 4% or less, and further preferably 3% or less. In the case where the boiling water shrinkage is greater than 5%, the cloth becomes hard due to the yarn shrinkage caused by heat shrinkage.

[0043] In addition, the modulus of elasticity at an elongation of 20% of the polytrimethylene terephthalate fiber of the present application needs to be 5 cN / dtex or less, preferably 4 cN / dtex or less, and further preferably 3 cN / dtex or less. If the modulus of elasticity at an elongation of 20% is greater than 5 cN / dtex, the cloth becomes hard through subsequent dyeing processing and the like.

[0044] Further, the birefringence Δn of the polytrimethylene terephthalate fiber of the present application is preferably 0.040 to 0.08. The birefringence Δn is more preferably 0.045 to 0.075, and the birefringence Δn is further preferably 0.050 to 0.070. When the birefringence Δn is less than 0.040, the yarn strength becomes small, the cloth is elongated due to external force, and it is difficult to maintain the form, and thus is not preferable.

[0045] Further, the specific gravity, which is a substitute index for the crystallinity of the polytrimethylene terephthalate fiber of the present application, is preferably 1.350 or less, and further preferably 1.319 or more and 1.350 or less. When the specific gravity is less than 1.319, in the stretch false twist processing, the yarn becomes brittle, and the yarn breakage frequently occurs, and the stretch false twist processing becomes difficult. On the other hand, in the case where the specific gravity is more than 1.350, the fuzz frequently occurs, and thus is not preferable.

[0046] Further, the peak of the thermal stress of the polytrimethylene terephthalate fiber of the present application is preferably present at 50°C to 100°C. When the peak is present at a temperature lower than 50°C, the heat resistance becomes low, and thus is not preferable. Further, when the peak is present at a temperature higher than 100°C, the crystallinity is too high, and the soft drape is lost, and thus is not preferable.

[0047] Further, the peak value of the thermal stress of the polytrimethylene terephthalate fiber of the present application is preferably 0.2 cN / dtex or less. If the peak value of the thermal stress is more than 0.2 cN / dtex, the deformation due to the hot water treatment such as dyeing increases, and thus in the production of cloth, the yarn shrinks to become hard in the texture, and thus is not preferable.

[0048] Further, the breaking strength of the polytrimethylene terephthalate fiber of the present application is 1.5 cN / dtex or more to 3.5 cN / dtex, preferably 1.7 cN / dtex to 3.3 cN / dtex, and further preferably 2.0 cN / dtex to 3.0 cN / dtex.

[0049] In the case where the breaking strength of the polytrimethylene terephthalate fiber is less than 1.5 cN / dtex, the durability of the product decreases, and thus is not preferable. Further, in the case where the breaking strength of the polytrimethylene terephthalate fiber is more than 3.5 cN / dtex, the crystallinity becomes too high, and the soft drape is lost, and thus is not preferable.

[0050] The breaking elongation of the polytrimethylene terephthalate fiber is preferably 30% to 100%. In the case where the breaking elongation of the polytrimethylene terephthalate fiber is less than 30%, the crystallinity becomes too high, and the soft drape is lost, and thus is not preferable. On the other hand, in the case where the breaking elongation of the polytrimethylene terephthalate fiber is more than 100%, when a load is applied to the fiber, the fiber is elongated, and the dimensional stability is not excellent, and thus is not preferable.

[0051] (3) Method for producing polytrimethylene terephthalate fiber

[0052] The polytrimethylene terephthalate fiber as described above can be produced, for example, by the following production method.

[0053] First, a polytrimethylene terephthalate fiber having an elongation at break of 50 to 200% is melt-solidified, and then wound at a winding speed of 1000 m / min or more. Subsequently, the fiber is heated using a heating roll at a temperature of the glass transition point of the polytrimethylene terephthalate ± 20°C, and then stretched by 1.0 to 2.0 times. Further, the fiber is wound on a heating roll at 50 to 150°C, and then temporarily wound at a speed of 2000 to 4800 m / min to form a flat round package.

[0054] A polytrimethylene terephthalate fiber having an elongation at break of 50 to 200% thus wound into a flat round package is stretched by 1.1 times or more at a temperature below the glass transition point of the polytrimethylene terephthalate, and then shrunk at a rate of 0.5 to 0.9 times while being heated, whereby a polytrimethylene terephthalate fiber having a small heat-induced shrinkage and capable of forming a cloth having a soft texture can be obtained.

[0055] At this time, the total stretching rate represented by the product of the stretching rate at a temperature below the glass transition point and the shrinkage rate upon heating is preferably 0.9 to 1.25 times, and further preferably 0.95 to 1.20 times. In the case where the total stretching rate is less than 0.90 times, the yarn sometimes relaxes, and the running of the yarn upon stretching becomes unstable to become a cause of broken yarn, and thus is not preferred. In the case where the total stretching rate is more than 1.25 times, the shrinkage rate of the yarn is too high, and in forming a cloth, a soft texture sometimes cannot be obtained, and thus is not preferred.

[0056] Note that a polytrimethylene terephthalate fiber obtained by melt-solidification, for example, can be manufactured by winding at a winding speed of 1000 m / min or more, and then stretching at a low rate of 1.0 to 2.0 times at a temperature of the glass transition point of the polytrimethylene terephthalate ± 20°C.

[0057] Further, the fiber can be wound on a heating roll at a speed of 4000 m / min or more, and wound using a winder. In these methods, it is also not problematic to heat using a heating roll at 50 to 150°C before winding, with the aim of suppressing the winding-up when the polytrimethylene terephthalate fiber is directly wound using a winder.

[0058] The high-elongation polytrimethylene terephthalate fiber thus obtained preferably has an elongation at break of 50% or more. More preferably, it has an elongation at break of 60 to 190%, and further preferably, it has an elongation at break of 70 to 180%.

[0059] In the case where the high elongation polypropylene terephthalate fiber has an elongation at break of less than 50%, the crystallinity of the fiber increases, and a soft fabric cannot be obtained, and thus is not preferable. On the other hand, if the elongation at break is more than 200%, the fiber does not crystallize when stretched at a temperature below the glass transition point, the strength significantly decreases, and the durability is low when the fiber is made into a fabric, and thus is not preferable.

[0060] Next, the polypropylene terephthalate fiber obtained by solidifying after melting is stretched at a temperature below the glass transition point of polypropylene terephthalate, further preferably at a temperature of 5°C or less below the glass transition point, further preferably at a temperature of 10°C or less below the glass transition point, by 1.1 times or more, further preferably by 1.2 times or more, further preferably by 1.3 times or more.

[0061] At this time, in the case where the fiber is stretched at a temperature higher than the glass transition point, the crystallinity increases, and a soft fabric cannot be obtained, and thus is not preferable. In addition, in the case where the fiber is stretched at a ratio lower than 1.1 times, the durability is low when the fiber is made into a fabric, and thus is not preferable.

[0062] In addition, the fiber obtained by stretching does not crystallize, and the polymer exhibits high orientation, and thus the dimensional stability due to heat is low, and thus by shrinking the fiber while heating at a ratio of 0.5 times or more to 0.9 times or less, the dimensional stability and durability can be improved.

[0063] At this time, in the case where the fiber is shrunk by less than 0.5 times, the oriented crystallinity of the polypropylene terephthalate fiber obtained is too low, and the durability is low when the fiber is made into a fabric, and thus is not preferable. In addition, in the case where the fiber is shrunk by more than 0.9 times, the crystallinity increases, and a soft fabric cannot be obtained, and thus is not preferable.

[0064] (4) Polyester-based fiber (core yarn)

[0065] In the present application, the above polypropylene terephthalate fiber and the polyester-based fiber are mixed by air texturing to obtain an air mixed yarn.

[0066] As the polyester-based fiber used at this time, a fiber obtained by spinning and stretching a polypropylene terephthalate (PTT) fiber, a polyethylene terephthalate (PET) fiber, a side-by-side or eccentric core-sheath composite fiber of polypropylene terephthalate and polyethylene terephthalate, a side-by-side or eccentric core-sheath composite fiber of polypropylene terephthalate and polypropylene terephthalate, a side-by-side or eccentric core-sheath composite fiber of polyethylene terephthalate and polyethylene terephthalate, and the like, by a conventional method can be preferably exemplified. In addition, an antistatic agent, a flame retardant, a heat-resistant agent, a weather-resistant agent, titanium oxide, and the like, can be added as an additive.

[0067] In such a polyester-based fiber, in order to apply a heat treatment or the like to the air laid yarn, the filament length difference between the core yarn and the sheath yarn is preferably increased, and the boiling water shrinkage is preferably 7 to 50%.

[0068] (5) Method for manufacturing air laid yarn

[0069] Next, the above-mentioned polytrimethylene terephthalate fiber as the sheath yarn and the above-mentioned polyester-based fiber as the core yarn are interlaced at 30 to 150 pieces per meter by air processing (Interlace or Taslan (registered trademark)), and are pulled by a roller, whereby an air laid yarn is obtained. The overfeed at the time of air laid processing is preferably 0.5 to 2%.

[0070] Further, the air laid yarn of the present application can also include a fiber having a cross-sectional shape other than a circular cross-sectional shape. For example, it can be composed of a fiber having a cross-sectional shape of a cross, a triangle, or a star, and the like, and if so, a unique texture can be obtained. Here, the degree of irregularity of the fiber having a cross-sectional shape other than a circular cross-sectional shape is a value calculated by measuring the maximum inscribed circle diameter r and the minimum circumscribed circle diameter R of the cross-sectional shape of the fiber, and the degree of irregularity = R / r, and the value of the degree of irregularity = R / r is preferably 1.15 to 10.0, and further preferably 1.2 to 10.0. When the degree of irregularity is less than 1.15, the difference from a circular cross-sectional shape can be small. In addition, if the degree of irregularity exceeds 10.0, the difference in orientation between the outside and the inside of the cross-sectional shape of the fiber increases at the time of spinning, and the obtained yarn can often be fluffed and relaxed, and is not suitable for processing. Figure 1

[0071] In addition, as the fiber having a cross-sectional shape other than a circular cross-sectional shape, a flat cross-sectional fiber is also exemplified. This is preferable because a unique texture can be obtained by using a flat cross-sectional fiber. Here, the degree of flatness of the flat cross-sectional fiber is a value calculated by drawing a rectangle circumscribing the cross-sectional shape of the fiber and measuring the long side L and the short side H, and the degree of flatness = L / H, and in the present application, the value of the degree of flatness = L / H is preferably 2.0 to 10.0. When the degree of flatness is less than 2.0, the difference from a circular cross-sectional shape can be small. In addition, if the degree of flatness exceeds 10.0, fluffing can easily occur at the time of spinning, and the stability is poor. Figure 2

[0072] The air laid yarn thus obtained can be a core-sheath type air laid yarn in which a low-shrinkage fiber composed of polytrimethylene terephthalate having a soft texture is used as the sheath yarn, and the filament length difference between the core and the sheath is large.

[0073] (6) Method for manufacturing core-sheath type air laid yarn

[0074] ​​In the present application, by subjecting the above air laid filament to a heat treatment such as dyeing processing, it is possible to obtain a core-sheath type air laid filament comprising a core filament and a sheath filament, with the above polytrimethylene terephthalate fiber serving as the sheath filament and the above polyester-based fiber serving as the core filament.

[0075] In such an air laid filament, the single fiber fineness of the sheath filament needs to be 0.3 to 10 dtex, more preferably 0.5 to 8 dtex, and further preferably 0.6 to 5 dtex. In the case where the single fiber fineness is greater than 10 dtex, the cloth or fabric loses softness due to the thick single fiber. On the other hand, in the case where the single fiber fineness is less than 0.3 dtex, it can be difficult to produce the fiber because of frequent occurrence of filament breakage. The number of single fibers (filament number) of the sheath filament is preferably 20 to 150.

[0076] On the other hand, the single fiber fineness of the core filament is preferably 1.0 to 5.0 dtex. The number of single fibers (filament number) of the core filament is preferably 12 to 100.

[0077] In addition, in the core-sheath type air laid filament of the present application, the total fineness needs to be 30 to 400 dtex, and more preferably 50 to 200 dtex. In the case where the total fineness is less than 30 dtex, it can be difficult to perform air laying because of the excessively thin total fineness. On the other hand, in the case where the total fineness is greater than 400 dtex, the cloth or fabric can lose softness. It should be noted that the number of single fibers (filament number) is preferably 40 to 400 (more preferably 40 to 200).

[0078] In the above core-sheath type air laid filament, it is important that the filament length difference between the core filament and the sheath filament defined below is 5% or more (more preferably 6 to 40%). In the case where the filament length difference is less than 5%, sufficient fluffiness is not obtained.

[0079] The above filament length difference is calculated by the following formula, after the above air laid filament is treated in boiling water, a load of 0.1 cN (0.098 g) x total fineness (dtex) of the air laid filament is applied, the air laid filament is cut into a length of 5 cm, the polyester-based fiber A (single fiber) and the polytrimethylene terephthalate fiber B (single fiber) are taken out from the cut air laid filament, a load of 0.1 cN (0.098 g) x single fiber fineness (dtex) is applied to each of them, and the lengths are measured.

[0080] Filament length difference (%) = (LB - LA) / LA x 100

[0081] wherein LA is the filament length (cm) of the polyester-based fiber of the core filament, and LB is the filament length (cm) of the polytrimethylene terephthalate fiber of the sheath filament.

[0082] In addition, in the core-sheath type air laid filament of the present application, the polytrimethylene terephthalate fiber of the sheath filament is preferably 50 to 90% by weight of the air laid filament (more preferably 60 to 80%). In the case where the polytrimethylene terephthalate fiber of the sheath filament is less than 50% by weight, not only a soft feel cannot be obtained, but also a dyeing difference between the core filament and the sheath filament can be easily seen.

[0083] (7) Method for producing fabric composed of core-sheath type air laid filament

[0084] In the present application, after a fabric (grey fabric) is obtained by weaving using the above-mentioned air laid filament, dyeing processing and sweat-absorbing processing are appropriately performed to obtain a fabric as a product. At this time, a difference in filament length between the sheath filament and the core filament of the air laid filament is exhibited by heat treatment of the dyeing processing, and a fabric composed of the core-sheath type air laid filament is obtained.

[0085] Here, the fabric can be composed of only the core-sheath type air laid filament, or can be composed of the core-sheath type air laid filament and other filaments. At this time, the other filaments are not particularly limited, and can be any one of crimpless filament, false twist crimping processed filament, latent crimp filament, spun filament, etc.

[0086] The weave of the fabric is not particularly limited, and can be any one of a woven fabric and a knitted fabric. For example, a woven fabric having a weave such as rib weave, float weave, double rib weave, circular rib weave, guipure weave, plating weave, plain weave, half cardigan weave, etc., a woven fabric having a weave such as plain weave, twill weave, and satin weave, etc. can be exemplified, but is not limited to these. The number of layers can be a single layer, or can be a plurality of layers of two or more layers.

[0087] Next, a textile product such as sportswear, a coat, an undergarment, men's clothing, women's clothing, a nursing garment, a workwear, a car seat cover material, and bedding, etc. can be produced using the above-mentioned fabric. Since such a fabric and a fiber product use the above-mentioned air laid filament, a soft feel and bulkiness are excellent.

[0088] Example

[0089] Hereinafter, an example and a comparative example of the present application will be described in detail, but the present application is not limited to these. It should be noted that each measurement item in the example is measured by the following method.

[0090] (1) Limiting viscosity [η]

[0091] The limiting viscosity [η] is obtained by extrapolating the specific viscosity ηsp and the concentration C (g / 100 ml) in o-chlorophenol at 35°C to a concentration of zero, and according to the following formula (1).

[0092] [η] = lim (ηsp / C) ・・・ (1)

[0093] C→0

[0094] (2) Glass transition point

[0095] The glass transition point was determined from the temperature rising curve obtained by DSC under a nitrogen atmosphere at a temperature rising rate of 10°C / min from room temperature to 300°C, after a prescribed amount of polymer chips was charged into an aluminum sample pan.

[0096] (3) Filament fineness (filament fineness of a multifilament)

[0097] The filament fineness of a multifilament was determined according to JIS-L-1013. In addition, the single filament fineness was calculated by dividing this value by the number of single filaments of the multifilament.

[0098] (4) Boiling water shrinkage (BWS)

[0099] According to JIS-L-1013, the fiber was crimped using a length measuring device having a frame circumference of 1.125 m, an initial load of 1 / 30 g of Decitex was applied, the yarn was twisted for 20 turns, a load of Decitex / 1.11 g was applied, and the twisted length was measured. Next, the load was removed, the twisted yarn was immersed in hot water at 100°C for 30 minutes, taken out, naturally dried, the load was applied again, the twisted length was measured, and the boiling water shrinkage was calculated by the following equation.

[0100] Boiling water shrinkage (%) = {(L0-L1) / L0} x 100

[0101] Here, L0; twisted yarn length before immersion (mm), L1; twisted yarn length after immersion (mm)

[0102] (5) Breaking strength, breaking elongation

[0103] According to JIS-L-1013, using a Tensilon manufactured by Orientech Corporation as a constant rate of extension type tensile testing machine, the measurement was performed at a clamping distance of 20 cm and a tensile speed of 20 cm / min.

[0104] (6) Modulus at 20% elongation

[0105] According to JIS-L-1013, using a Tensilon manufactured by Orientech Corporation as a constant rate of extension type tensile testing machine, the measurement was performed at a clamping distance of 20 cm and a tensile speed of 20 cm / min. The slope of the tangent line of the SS curve at 20% elongation was calculated as the modulus at 20% elongation.

[0106] (7) Specific gravity

[0107] The specific gravity of the sample was determined according to the sink-float method of JIS-L-1013 8.17.1.

[0108] (8) Birefringence Δn

[0109] According to the Fiber Handbook - Raw Materials, p. 969 (5th printing, published by Maruzen Co., Ltd., 1978), using an optical microscope and a compensator, the birefringence is determined by observing the retardation of polarized light on the surface of the fiber.

[0110] (9) Temperature at which the maximum thermal stress exists and the maximum thermal stress

[0111] A KE-2 manufactured by Kurofune Engineering Co. was used. The measurement was performed at an initial load of 0.044 cN / dtex and a temperature increase rate of 100°C / min. The data obtained were plotted as a temperature-thermal stress curve with the horizontal axis as the temperature and the vertical axis as the thermal stress. The temperature and the thermal stress at the point where the differential coefficient of the temperature-thermal stress curve changed from positive to negative were determined, and the maximum stress was determined by dividing the stress by the fineness.

[0112] (10) Number of interlacements

[0113] The air-textured yarn was cut to a length of 1 m under a load of 8.82 mN x tex (0.1 g / dtex), and after the load was removed, it was left to relax at room temperature for 24 hours, and then the number of nodes was read and expressed as pieces / m.

[0114] (11) Yarn length difference

[0115] The yarn was treated in the same manner as the above boiling water shrinkage, and then a load of 0.1 cN (0.098 g) x the total fineness (dtex) of the air-textured yarn was applied, and it was cut to a length of 5 cm. The polyester-based fiber A (single fiber) and the polytrimethylene terephthalate fiber B (single fiber) were taken out from the air-textured yarn thus cut, and a load of 0.1 cN (0.098 g) x the fineness (dtex) of the single fiber was applied to each of them, and the length was measured. The yarn length difference (%) was calculated by the following equation,

[0116] Yarn length difference (%) = (LB - LA) / LA x 100

[0117] where LA is the length of the polyester-based fiber of the core yarn (cm), and LB is the length of the polytrimethylene terephthalate fiber of the sheath yarn (cm).

[0118] (12) Hand

[0119] The tester touched the air-textured yarn with his hand, and evaluated it into three grades: O (having bulk and softness), Δ (ordinary), and X (lacking bulk or being hard).

[0120] [Example 1]

[0121] Dimethyl terephthalate and 1,3-propanediol were charged at a molar ratio of 1:2, and 0.1% by weight of tetrabutoxy titanium corresponding to dimethyl terephthalate was added, and the ester exchange reaction was completed at a heating temperature of 240°C under normal pressure. Next, 0.1% by weight of tetrabutoxy titanium and 0.5% by weight of titanium dioxide corresponding to the theoretical polymer amount were further added, and the reaction was carried out at 270°C for 3 hours.

[0122] The obtained polymer consisted of 100 mole% of terephthalic acid propylene glycol ester repeating units, and had an intrinsic viscosity of 1.0 dl / g. In addition, the glass transition point of the obtained polymer was 51°C.

[0123] The obtained polymer was dried by a conventional method, and after the moisture content reached 50 ppm, it was melted at 265°C and extruded through a single row of 36 holes each having a diameter of 0.27 mm.

[0124] The extruded melt multi-filament was rapidly cooled by contacting it with air at a wind speed of 4.0 m / min to convert it into a solid multi-filament, and then an oil agent containing 60% by weight of octyl stearate, 15% by weight of polyoxyethylene alkyl ether, and 3% by weight of potassium phosphate was prepared into an aqueous emulsion having a concentration of 10% by weight, and the fiber was coated with the oil agent at an oil agent adhesion amount of 0.6% by weight using a guide nozzle.

[0125] Next, the solid multi-filament was wound around a roll heated to 50°C at a peripheral speed of 2100 m / min, and then wound around a roll heated to 80°C at a stretch of 1.3 times, and then wound using a winder in which the main shaft and the contact roll were simultaneously driven at a winding speed of 2600 m / min to obtain a fiber wound flat round package of 72 dtex / 36 filaments.

[0126] Then, the fiber wound around the package was stretched by 1.5 times at 30°C, and heated using a contact type hot plate heater at 190°C to shrink the fiber by 0.7 times, and wound at a speed of 600 m / min to obtain a low shrinkage polypropylene terephthalate fiber (sheath filament yarn).

[0127] On the other hand, as a core filament yarn, a polyester (polyethylene terephthalate) drawn yarn (total filament count 56 dtex / 36, boiling water shrinkage 10%) was prepared.

[0128] Next, the above sheath filament yarn and the core filament yarn were aligned, and interwoven at an overfeed rate of 1.5% to obtain an air mixed filament having an interwoven number of 69 / m. The properties of the obtained polypropylene terephthalate fiber are shown in Table 1, and the properties of the mixed filament are shown in Table 2.

[0129] [Example 2]

[0130] After the polymer was produced in the same manner as in Example 1, the obtained polymer was dried by a conventional method so that the moisture content reached 50 ppm, and then extruded through a double-row arrayed spinning port having 72 holes each with a diameter of 0.23 mm at 265°C.

[0131] The extruded molten multifilament was subjected to oil agent application in the same manner as in Example 1, and then the solid multifilament was wound around a roll heated to 50°C at a peripheral speed of 2100 m / min, wound around a heated roll at 80°C at a stretch of 1.3 times, and then wound up at a winding speed of 2600 m / min using a winder of a type in which a main shaft and a contact roll are simultaneously driven, to obtain a fiber-wound flat-round-shaped package of 72 dtex / 72 filaments.

[0132] Then, the fiber wound around the package was stretched by 1.4 times at 30°C, heated using a contact-type hot plate heater at 190°C, and shrunk by 0.75 times at a speed of 600 m / min to obtain a low-shrinkage polytrimethylene terephthalate fiber (sheath filament).

[0133] On the other hand, as a core filament, a polyester (polyethylene terephthalate) drawn yarn (total fineness: 56 dtex / 36, boiling water shrinkage: 13%) was prepared.

[0134] Next, the above sheath filament and the core filament were aligned, and interwoven in the same manner as in Example 1 at an overfeed rate of 1.5% to obtain an air mixed filament having an interwoven number of 71 / m. The properties of the obtained polytrimethylene terephthalate fiber are shown in Table 1, and the properties of the mixed filament are shown in Table 2.

[0135] [Example 3]

[0136] After the polymer was produced in the same manner as in Example 1, the obtained polymer was dried by a conventional method so that the moisture content reached 50 ppm, and then extruded through a single-row arrayed spinning port having 36 holes each with a diameter of 0.27 mm at 265°C.

[0137] The extruded molten multifilament was subjected to oil agent application in the same manner as in Example 1, and then the solid multifilament was wound around a roll heated to 50°C at a peripheral speed of 2350 m / min, wound around a heated roll at 80°C at a stretch of 1.1 times, and then wound up at a winding speed of 2600 m / min using a winder of a type in which a main shaft and a contact roll are simultaneously driven, to obtain a fiber-wound flat-round-shaped package of 72 dtex / 36 filaments.

[0138] Then, the fiber wound on the package was stretched 1.6 times at 30°C, heated with a contact heater of 190°C, and shrunk 0.65 times, and wound at a speed of 600 m / min to obtain a low-shrinkage polytrimethylene terephthalate fiber (filament for sheath).

[0139] On the other hand, as the filament for core, a composite drawn yarn (total denier 33 dtex / 24, boiling water shrinkage 21%) of polyethylene terephthalate and polytrimethylene terephthalate was prepared.

[0140] Next, the above filament for sheath and the filament for core were drawn in line, and interwoven in the same manner as in Example 1 with an overfeed ratio of 1.5% to obtain an air mixed filament having an interwoven number of 71 / m. The properties of the obtained polytrimethylene terephthalate fiber are shown in Table 1, and the properties of the mixed filament are shown in Table 2.

[0141] [Example 4]

[0142] After the polymer was produced in the same manner as in Example 1, the obtained polymer was dried by a conventional method so that the moisture content reached 50 ppm, and then extruded through a single row of spinning ports opened by 36 holes having a diameter of 0.27 mm at 265°C.

[0143] The extruded molten multifilament was subjected to oil agent attachment in the same manner as in Example 1, and then wound on a roll heated to 50°C at a peripheral speed of 3000 m / min, and then wound on a roll heated at 80°C at a stretch of 1.2 times, and then wound at a winding speed of 3600 m / min using a winder in which the main shaft and the contact roll were simultaneously driven to obtain a fiber-wound oblong package of 56 dtex / 36 filaments.

[0144] Then, the fiber wound on the package was stretched 1.6 times at 30°C, heated with a contact heater of 190°C, and shrunk 0.65 times, and wound at a speed of 600 m / min to obtain a low-shrinkage polytrimethylene terephthalate fiber (filament for sheath).

[0145] On the other hand, as the filament for core, a composite drawn yarn (total denier 33 dtex / 24, boiling water shrinkage 21%) of polyethylene terephthalate and polytrimethylene terephthalate was prepared.

[0146] Next, the above filament for sheath and the filament for core were drawn in line, and interwoven in the same manner as in Example 1 with an overfeed ratio of 1.5% to obtain an air mixed filament having an interwoven number of 71 / m. The properties of the obtained polytrimethylene terephthalate fiber are shown in Table 1, and the properties of the mixed filament are shown in Table 2.

[0147] [Examples 5-6]

[0148] Example 1 was carried out in the same manner as in Example 1 except that the cross-sectional shape of the sheath filament and the number of filaments were changed as shown in Table 1. The properties of the obtained polytrimethylene terephthalate fiber are shown in Table 1, and the properties of the conjugate filament are shown in Table 2.

[0149] [Comparative Example 1]

[0150] After the polymer was produced in the same manner as in Example 1, the obtained polymer was dried by a conventional method so that the moisture content reached 50 ppm, and then extruded through a single row of spinneret openings opened by 36 holes having a diameter of 0.27 mm at 265°C.

[0151] The extruded molten conjugate filament was subjected to oil agent application in the same manner as in Example 1, and then wound on a roll heated to 55°C at a peripheral speed of 1500 m / min, and then wound on a heated roll at 130°C at a stretch of 2.1 times, and then wound on a take-up machine using a simultaneous driving of the main shaft and the contact roll at a take-up speed of 3000 m / min to obtain a wound flat round package of 72 dtex / 36 filament of the fiber (polytrimethylene terephthalate fiber filament for sheath).

[0152] On the other hand, as the core filament, a polyester (polyethylene terephthalate) drawn yarn (total fineness 56 dtex / 36, boiling water shrinkage 12%) was prepared.

[0153] Next, the above-mentioned sheath filament and the core filament were aligned, and interwoven in the same manner as in Example 1 at an overfeed rate of 1.5% to obtain an air conjugate filament having an interwoven number of 65 / m. The properties of the obtained polytrimethylene terephthalate fiber are shown in Table 1, and the properties of the conjugate filament are shown in Table 2.

[0154] The obtained air conjugate filament had a small difference in filament length between the core and the sheath, and lacked bulkiness.

[0155] [Comparative Example 2]

[0156] After the polymer was produced in the same manner as in Example 1, the obtained polymer was dried by a conventional method so that the moisture content reached 50 ppm, and then extruded through a single row of spinneret openings opened by 36 holes having a diameter of 0.27 mm at 265°C.

[0157] The extruded molten multifilaments were subjected to oil agent attachment in the same manner as in Example 1, and then, after winding the solid multifilaments on a roll heated to 55°C at a peripheral speed of 1500 m / min, the multifilaments were wound on a heated roll at 130°C at a 2.1-fold stretch, and then, using a winder of the type in which the main shaft and the contact roll are simultaneously driven, the multifilaments were wound at a winding speed of 3000 m / min, to obtain a fiber-wound flat-round package of 56 dtex / 36 filaments.

[0158] Then, the fiber wound on the package was stretched by 1.05-fold at 30°C, and heated using a contact-type hot plate heater at 190°C, and the fiber was shrunk by 0.92-fold, and wound at a speed of 600 m / min, to obtain a polytrimethylene terephthalate fiber (filament for sheath).

[0159] On the other hand, as a filament for core, a polyester (polyethylene terephthalate) drawn yarn (total fineness 56 dtex / 36, boiling water shrinkage 10%) was prepared.

[0160] Next, the above filament for sheath and the filament for core were aligned, and interlaced in the same manner as in Example 1 at an overfeed rate of 1.5%, to obtain an air laid multifilament having an interlaced number of 63 / m. The properties of the obtained polytrimethylene terephthalate fiber are shown in Table 1, and the properties of the air laid multifilament are shown in Table 2.

[0161] The sheath filament of the obtained air laid multifilament was hard, and had a poor texture.

[0162]

[0163]

[0164] Industrial applicability

[0165] According to the present application, it is possible to provide a low shrinkage fiber and a method for producing the same, which is substantially composed of polytrimethylene terephthalate and which can produce a raw yarn for cloth and fabric having a small shrinkage due to heat and a soft texture, and an air laid multifilament containing the polytrimethylene terephthalate fiber and a cloth and fabric composed of the same, and thus has a great industrial value.

Claims

1. A polypropylene terephthalate fiber, characterized in that, The fiber is composed of 90 mol% or more of repeating propylene terephthalate units, the boiling water shrinkage rate of the propylene terephthalate fiber is less than 5%, and the elastic modulus of the propylene terephthalate fiber at an elongation of 20% is less than 5 cN / dtex.

2. The polypropylene terephthalate fiber according to claim 1, wherein, The birefringence Δn of polypropylene terephthalate fiber is above 0.040 and the specific gravity is below 1.

350.

3. The polypropylene terephthalate fiber according to claim 1 or 2, wherein, The peak of thermal stress in polypropylene terephthalate fiber exists between 50 and 100°C, and the peak value of thermal stress is below 0.2 cN / dtex.

4. The polypropylene terephthalate fiber according to claim 1 or 2, wherein, The tensile strength of polypropylene terephthalate fiber is 1.5–3.5 cN / dtex, and the elongation at break is 30–100%.

5. A method for manufacturing polypropylene terephthalate fiber, characterized in that, Polypropylene terephthalate consisting of repeating units of 90 mol% or more is melt-cured, wound at a winding speed of 1000 m / min or more, and then stretched by more than 1.1 times at a temperature below the glass transition point of the polypropylene terephthalate. Then, the fiber is shrunken at a ratio of 0.5 to 0.9 times while being heated.

6. An air-blended fiber, characterized in that, The fiber comprises polypropylene terephthalate fiber and polyester fiber as described in any one of claims 1 to 4.

7. The air-blended fiber according to claim 6, wherein, The boiling water shrinkage rate of polyester fibers is 7-50%.

8. The air-blended fiber according to claim 6 or 7, comprising irregularly shaped cross-section fibers.

9. A core-sheath type air-blended fiber, characterized in that, The air-blended fiber described in claim 6 is obtained by heat treatment and is an air-blended fiber with a total fineness of 30 to 400 dtex, consisting of a core fiber and a sheath fiber. The core fiber is composed of polyester fiber, and the sheath fiber is composed of polypropylene terephthalate fiber with a single fiber fineness of 0.3 to 10 dtex. Furthermore, the difference in fiber length between the core fiber and the sheath fiber, as defined by the following method, is 5% or more. The method for determining the difference in filament length is as follows: After treating the blended fibers in boiling water, a load of 0.1 cN (0.098 g) × the total fineness (dtex) of the air-blended fibers was applied, and the fibers were cut into 5 cm lengths. Polyester fiber A (monofiber) and polypropylene terephthalate fiber B (monofiber) were taken out from the cut air-blended fibers, and a load of 0.1 cN (0.098 g) × the single fiber fineness (dtex) was applied to each fiber, and the lengths were measured. The fiber length difference (%) was calculated using the following formula. Filament length difference (%) = (LB - LA) / LA × 100 Where LA is the length (cm) of the polyester fiber core and LB is the length (cm) of the polypropylene terephthalate fiber sheath.

10. The core-sheath type air-blended fiber according to claim 9, wherein, The weight ratio of the sheath filament to the total weight of the core-sheath type air-blended filament is 50-90%.

11. The core-sheath type air-blended fiber according to claim 9 or 10, comprising irregularly shaped cross-section fibers.

12. A fabric comprising air-blended fibers as claimed in any one of claims 6 to 8.

13. A fabric comprising the core-sheath type air-blended fiber as described in any one of claims 9 to 11.

Citation Information

Patent Citations

  • Poly(1,3-propylene terephthalate)

    JP1993262862A

  • High performance brush

    JP1996173244A

  • Production of poly(Trimethylene terephthalate) yarn

    JP1997003724A

  • Polyester yarn and method for producing the same

    JP2001207329A

  • Polyester fiber and method for producing the same

    JP2001348729A

Cited By

  • Self-crimp high-fluffy yarn based on high-shrinkage-difference fiber blending and preparation method of self-crimp high-fluffy yarn

    CN122105708A

  • Self-curling high-bulkiness yarn based on high-shrinkage differential fiber blending and preparation method thereof

    CN122105708B